2022
DOI: 10.3390/biom12070984
|View full text |Cite
|
Sign up to set email alerts
|

Src Family Kinases: A Potential Therapeutic Target for Acute Kidney Injury

Abstract: Src family kinases (SFKs) are non-receptor tyrosine kinases and play a key role in regulating signal transduction. The mechanism of SFKs in various tumors has been widely studied, and there are more and more studies on its role in the kidney. Acute kidney injury (AKI) is a disease with complex pathogenesis, including oxidative stress (OS), inflammation, endoplasmic reticulum (ER) stress, autophagy, and apoptosis. In addition, fibrosis has a significant impact on the progression of AKI to developing chronic kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 153 publications
(226 reference statements)
3
7
0
Order By: Relevance
“…c‐Src belongs to the Src family of tyrosine kinases (SFKs) and shares structural homology with other family members, including Fyn, c‐Yes, Lck, and Fgr. [ 42 , 43 ] In SFKs, all members have a highly conserved tyrosine residue (Tyr530 in c‐Src) in the tail region that once phosphorylated, remains in an inactive conformation. [ 36 , 44 ] However, the N‐terminal unique domain, which is the only non‐conserved region within the kinase family, is specific to c‐Src.…”
Section: Discussionmentioning
confidence: 99%
“…c‐Src belongs to the Src family of tyrosine kinases (SFKs) and shares structural homology with other family members, including Fyn, c‐Yes, Lck, and Fgr. [ 42 , 43 ] In SFKs, all members have a highly conserved tyrosine residue (Tyr530 in c‐Src) in the tail region that once phosphorylated, remains in an inactive conformation. [ 36 , 44 ] However, the N‐terminal unique domain, which is the only non‐conserved region within the kinase family, is specific to c‐Src.…”
Section: Discussionmentioning
confidence: 99%
“…Src family kinases (SFKs) play a key role in regulating the autophagy of renal resident cells. [ 19 ] Thus, we assessed the expression patterns of SFKs in the podocytes treated with HG with or without NCOA3 lentivirus. Our results showed that among SFKs, only the mRNA level of Fyn was induced by HG, and downregulated by NCOA3 overexpression significantly ( Figure 3 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al highlighted the significance of the Lyn family of SFKs. Lyn is of particular importance because its deficiency has led to the pathogenesis of many different diseases [302]. For instance, in mice, Lyn knockout exacerbates lipopolysaccharide-induced lung inflammation, and the mechanism involves NF-κB activation [303].…”
Section: Src Family Kinasesmentioning
confidence: 99%